(untitled) (Citizenship in Action: Extension and Culture Magazine, 2025)
This report describes the outreach activities carried out at the Federal University of the State of Rio de Janeiro (UNIRIO) with beneficiaries of the project “Democratization of Access to Culture, Sports, and Citizenship Practices in Assisted Centers in the Baixada Fluminense Region.” The initiative aimed to bring the university closer to the community by inviting children and young people to visit the institution’s academic spaces, providing them with direct contact with the university environment. It was observed that the experience contributed to broadening the children’s educational perspectives, awakening their interest in knowledge and encouraging their active participation. The results indicate that the action was well received by the participating public and that it helped to strengthen the bond between the university and the community.